Eksistensi Kepala Lingkungan Sebagai Aktor dan Agen Pembangunan: Studi Antropologi Politik Tentang Struktur dan Kekuasaan - Edy Suhartono (Department of Anthropology, 2026)
This study examines the existential role of the Neighborhood Head (Kepala Lingkungan - Kepling) as both an actor and an agent of development within the urban governance structure of Medan City. The research was situated in two purposively selected neighborhoods, each representing distinct sub-districts: Helvetia Timur in Medan Helvetia District and Tanjung Mulia in Medan Deli District. Employing a descriptive qualitative design, the study utilized semi-structured interviews with the respective Kepling, complemented by documentary analysis and field data collection. The investigation pursues three interconnected objectives: (1) to delineate the general configuration of the Kepling's existence in Medan; (2) to ascertain their functional role as an actor; and (3) to identify their agency-oriented functions within the local social order. Analytically, the study draws upon Anthony Giddens' structuration theory, which reveals that the Kepling's role is predominantly operationalized as an extension of bureaucratic authority, acting as a downward conduit for tasks delegated by the lurah (sub-district head) and camat (district head). Concurrently, an application of Pierre Bourdieu's theory of practice furnishes compelling evidence of the embeddedness of the Kepling's actions within broader structures of power and social stratification. In executing their mandated duties, the Kepling operate in alignment with their internalized habitus, thereby inadvertently perpetuating and reproducing existing hierarchical and prescriptive power relations. Nonetheless, the dialectical nature of practice also accommodates latent possibilities for strategic resistance. Within the specific context of this inquiry, however, such resistance does not assume the form of overt contestation over political authority or capital accumulation. Instead, it manifests as a more subtle, reflexive endeavor to mobilize and optimize social capital, principally constituted by the community residents under their jurisdiction. This reservoir of social capital emerges as a strategically vital resource, enhancing the Kepling's bargaining position vis-à-vis the entrenched structural and power configurations that circumscribe their operational environment. Abstrak: Penelitian ini bertujuan mengkaji dan menganalisis eksistensi Kepala Lingkungan (Kepling) sebagai aktor sekaligus agen pembangunan di Kota Medan. Lokasi penelitian ditentukan pada dua lingkungan yang masing-masing berasal dari kelurahan berbeda, yaitu Kelurahan Helvetia Timur di Kecamatan Medan Helvetia dan Kelurahan Tanjung Mulia di Kecamatan Medan Deli. Untuk mencapai tujuan tersebut, penelitian menggunakan metode kualitatif deskriptif melalui wawancara mendalam terhadap Kepling di kedua lokasi, serta didukung oleh pengumpulan data dan dokumen pendukung. Secara spesifik, penelitian ini memiliki tiga tujuan utama: (1) memperoleh gambaran umum tentang eksistensi Kepling di Kota Medan, (2) mendeskripsikan peran Kepling sebagai aktor, dan (3) mendeskripsikan peran Kepling sebagai agen. Berdasarkan analisis menggunakan teori strukturasi Anthony Giddens, ditemukan bahwa peran Kepling di kedua wilayah cenderung lebih dominan sebagai aktor, yaitu menjalankan tugas yang merupakan perpanjangan dari fungsi lurah dan camat. Sementara itu, analisis dengan teori praktik Pierre Bourdieu menunjukkan indikasi kuat adanya keterkaitan antara praktik Kepling dengan struktur dan kekuasaan. Ketika Kepling menjalankan perannya sebagai aktor, mereka secara otomatis bertindak sesuai dengan habitus yang melekat, sehingga tanpa disadari turut memperkuat struktur sosial yang ada sekaligus mereproduksi struktur kekuasaan yang bersifat hierarkis dan instruktif. Namun, realitas praktik juga dapat dimaknai sebagai bentuk perlawanan strategis. Dalam konteks kajian ini, perlawanan tersebut tidak tampak sebagai perebutan kekuasaan atau akumulasi modal kapital, melainkan lebih pada upaya mengelola potensi modal sosial yang dimiliki, yakni para warga masyarakat di lingkungan masing-masing. Modal sosial inilah yang dinilai sangat strategis dan bermanfaat untuk meningkatkan posisi tawar (bargaining position) agen dalam menghadapi struktur dan kekuasaan yang ada.